A Nucleotide Binding Motif in Hepatitis C Virus (HCV) NS4B Mediates HCV RNA Replication - Einav, Shirit (American Society for Microbiology, 2004)
Hepatitis C virus (HCV) is a major cause of viral hepatitis. There is no effective therapy for most patients. We have identified a nucleotide binding motif (NBM) in one of the virus's nonstructural proteins, NS4B. This structural motif binds and hydrolyzes GTP and is conserved across HCV isolates. Genetically disrupting the NBM impairs GTP binding and hydrolysis and dramatically inhibits HCV RNA replication. These results have exciting implications for the HCV life cycle and novel antiviral strategies.